2018
DOI: 10.1080/15548627.2018.1489479
|View full text |Cite
|
Sign up to set email alerts
|

Specific autophagy and ESCRT components participate in the unconventional secretion of CFTR

Abstract: The most common mutation in cystic fibrosis patients is a phenylalanine deletion at position 508 (ΔF508) in the CFTR (cystic fibrosis transmembrane conductance regulator) gene. This mutation impairs cell-surface trafficking of CFTR. During cellular stress, core-glycosylated CFTRΔF508 is transported to the cell surface from the endoplasmic reticulum (ER) via an unconventional route that bypasses the Golgi. However, the mechanisms for this unconventional secretory pathway of CFTR are not well delineated. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(59 citation statements)
references
References 53 publications
0
59
0
Order By: Relevance
“…Interestingly, membrane proteins have also been shown to be recruited to the plasma membrane by secretory autophagy. Indeed, specific autophagy and ESCRT components participate in cystic fibrosis transmembrane conductance regulator (CFTR) unconventional secretion, thus suggesting that the autophagic machinery may play a specific role in cystic fibrosis pathogenesis [101].…”
Section: Non Degradative Function Of Autophagy: Secretory Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, membrane proteins have also been shown to be recruited to the plasma membrane by secretory autophagy. Indeed, specific autophagy and ESCRT components participate in cystic fibrosis transmembrane conductance regulator (CFTR) unconventional secretion, thus suggesting that the autophagic machinery may play a specific role in cystic fibrosis pathogenesis [101].…”
Section: Non Degradative Function Of Autophagy: Secretory Autophagymentioning
confidence: 99%
“…Conversely, other components of the macroautophagic machinery appear to be dispensable, such as Ulk1 [104], whereas some, such as the activation of the protein Rubicon, commit the cell to LAP, inhibiting autophagy [107]. LAP is involved in the response to pathogens [101], but also in the elimination of dead cells [108], including the finalization of the entotic process, by which cells engulf and cannibalize other cells [109].…”
Section: Non Degradative Function Of Autophagy: Secretory Autophagymentioning
confidence: 99%
“…Clearly, genetics tells us that GORASPs have a role in unconventional secretion. This conclusion is now supported by a large number of reports showing the involvement of GORASPs in other systems including mammalian cells (Feinstein & Linstedt, 2008;Noh et al, 2018;van Ziel, Largo-Barrientos, Wolzak, Verhage, & Scheper, 2019;Wu, Li, & Zhao, 2020). Although transport by COPII and COPI is not required for unconventional secretion, the essential role of GORASPs in this process suggests a link to the Golgi membranes.…”
Section: Discussionmentioning
confidence: 69%
“…The IRE1 kinase-ASK1 cascade was suggested to play a role in the initiation of autophagosome formation by modulating Beclin-1 (38). Components of the early autophagosome formation, such as autophagy related 5 (ATG5) and autophagy related 7 (ATG7), participate in the vesicular structures involved in ER stress-associated UPS of CFTR (14). In addition, IRE1 is an upstream signal that regulates the generation and anchoring of Sec16A at the ER exit sites, which increases the ER export of core-glycosylated CFTRs during UPS in response to ER stress (15).…”
Section: Discussionmentioning
confidence: 99%
“…Although recent studies have identified several key molecules associated with the UPS of membrane proteins (i.e., Sec16A in ER exit and early autophagy/multivesicular body components in the vesicular pathway for UPS of CFTR) (14,15), the entire complex of UPS regulatory mechanisms remains unknown. In general, most UPS is not constitutive but instead is stress induced (16).…”
Section: Introductionmentioning
confidence: 99%